Plant Expression of Hydrophobin Fused K39 Antigen for Visceral Leishmaniasis Immunodiagnosis - Silva, Bruno B.; Santos, Eduarda N. F. N.; Araújo, Lucelina S.; Bezerra, Arnaldo S.; Marques, Lívia É. C.; Tramontina Florean, Eridan O. P.; van Tilburg, Maurício F.; Guedes, Maria Izabel F. (Frontiers in Plant Science, 2021)
Visceral leishmaniasis is a Neglected Tropical Disease of high mortality caused by the protozoan Leishmania infantum. Its transmission cycle is complex, and it has in the domestic dog its main reservoir. The diagnostic tests currently used rely on prokaryotic systems’ proteins, but their low sensitivity increases the disease’s burden. The plant transient expression of recombinant proteins allows the production of complex antigens. However, this system has limited competitiveness against the bacterial production of purified antigens. Thus, we have shown that the L. infantum K39 antigen’s fusion to a hydrophobin allows its production for diagnostic tests without the need for intensive purification. The sera of naturally infected dogs specifically detect the semi-purified rK39-HFBI protein. The test validation against a panel of 158 clinical samples demonstrates the platform’s viability, resulting in sensitivity and specificity of 90.7 and 97.5%, respectively. Thus, the use of semi-purified antigens fused to hydrophobins can become the standard platform for large-scale antigens production to expand diagnostic tests for other human and veterinary diseases worldwide.